Multimodal ChatGPT-4V for Electrocardiogram Interpretation: Promise and Limitations - Lingxuan Zhu; Weiming Mou; Keren Wu; Yancheng Lai; Anqi Lin; Tao Yang; Jian Zhang; Peng Luo (JMIR Publications, 2024)
This study evaluated the capabilities of the newly released ChatGPT-4V, a large language model with visual recognition abilities, in interpreting electrocardiogram waveforms and answering related multiple-choice questions for assisting with cardiovascular care.